Conoce la nueva red de pluviómetros: Monitoreo de lluvias en tiempo real - Barrios Perez, Camilo; Amaya Quintero, Alejandra; Estrada Vargas, Oscar Hernan; Rivera Rivera, Ovidio; Salas Betancourt, Daniela (2025)
In this video, we present the automated rain gauge network implemented at the CIAT campus in collaboration with Cenicaña, which represents a strategic infrastructure for real-time precipitation monitoring. This network is composed of 10 spatially distributed digital rain gauges installed across the campus, capable of recording rainfall behavior minute by minute and transmitting information continuously and automatically. The rain gauges are fully autonomous, powered by solar panels, with an internal data storage system through a data logger and wireless data transmission via LoRa technology to a central server. The information is visualized through an intuitive application that dynamically displays the spatial and temporal distribution of rainfall, facilitating data-driven decision-making for site-specific management. The information generated by this network enables the analysis of the spatio-temporal variability of precipitation, supports irrigation management, agronomic crop management, the assessment of extreme events, and the strengthening of agroclimatic and water resource management studies.